Pengaruh Etos Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Adhya Adhikari Gemilang (Yoku Yatta Medan) - Silvianis Anjelina Zalogo; Ahmad Saputra; May Hendri (Skena Bisnis, 2024)
This study aims to determine how much influence Work Ethic and Work Discipline have on Employee Performance with Job Satisfaction as an intervening variable. The data collection method was through a survey circulating questionnaires on 62 Yoku Yatta Medan employees who were used as research samples. The analysis method is a validity test, reliability test, classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test. Analysis of hypothesis tests namely path coefficient, t test, determination coefficient test (R2), sobel test. The results showed (a) there was an influence of work ethic on job satisfaction of 4.895 with a significant level of 0.000 < 0.05 (b) there was an influence of work discipline on job satisfaction of 5.755 with a significant level of 0.000 < 0.05 (c) there was an influence of work ethic on employee performance of 2.483 with a significant level of 0.016 < 0.05 (d) there was an influence of work discipline on employee performance of 2.224 with a significant level of 0.030 < 0.05 (e) there is an effect of job satisfaction on employee performance of 5.334 with a significant level of 0.000 < 0.05 (f) job satisfaction mediates the relationship of work ethic to employee performance of 0.250 > 0.216 (g) job satisfaction mediates the relationship of work discipline to employee performance of 0.293 > 0.204. The conclusion of this study is that work ethic, work discipline affects job satisfaction and employee performance and job satisfaction can mediate work ethic and work discipline on employee performance at PT. Adhya Adhikari Gemilang (Yoku Yatta Medan).